2015
DOI: 10.1007/s12010-015-1499-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Total Phenol and Flavonoid Content and Antimicrobial Activities of Artocarpus altilis (Breadfruit) of Underutilized Tropical Fruit Extracts

Abstract: Artocarpus altilis (breadfruit) pulp, peel and whole fruit were extracted with various solvents such as hexane, dichloromethane (DCM) and methanol. The antioxidant activity of these extracts were examined using the stable 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test. IC50 was 55 ± 5.89 μg/ml for the pulp part of methanol extract. In the β-carotene bleaching assay, the antioxidant activity was 90.02 ± 1.51 % for the positive control (Trolox) and 88.34 ± 1.31 % for the pulp part of the fruit meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 22 publications
(21 reference statements)
2
37
0
7
Order By: Relevance
“…Naturally occurring flavonoids have been found to have beneficial effects on health, and these compounds have drawn attention because of their relative safety and accumulated evidence of anti-obesity and anti-diabetic effects in animals and humans [22]. GF, one of polyphenolic flavonoids, have been found to possess widespread biological functions and health benefits [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring flavonoids have been found to have beneficial effects on health, and these compounds have drawn attention because of their relative safety and accumulated evidence of anti-obesity and anti-diabetic effects in animals and humans [22]. GF, one of polyphenolic flavonoids, have been found to possess widespread biological functions and health benefits [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoids from this and other species have also been shown to have anti-inflammatory [5], anti-oxidative [7], hemostatic [8], anti-hypertensive [9], antihypercholesterolemic [10] and anti-atherosclerotic activities [11].…”
Section: Introductionmentioning
confidence: 95%
“…A comparative study has been conducted on the antioxidant properties of the pulp, peel and whole fruit of A. altilis extracted with hexane, dichloromethane and methanol (Jalal et al, 2015). Results Baba, et al: Two important fruits of Oceania showed that the highest values were from the methanol pulp extract with total phenolic content of 780 mg GAE/g, total flavonoid content of 6210 mg QE/g, DPPH radical scavenging IC 50 of 55 μg/ml and β-carotene bleaching ability of 88%.…”
Section: Phytochemistry and Pharmacology Of Fruitsmentioning
confidence: 99%
“…Breadfruit ( Artocarpus altilis ) has been a traditional crop in tropical and subtropical regions because it offers multifarious uses for medicine, animal feed, and the consumption of starchy fruit, mostly by the underprivileged population . In the last decades, its annual production has reached approximately 2 × 10 6 tons around the world…”
Section: Introductionmentioning
confidence: 99%